A survey of E-learning Implementation Best Practices in Jordanian Government Universities - Altarawneh, Haroon Salem (International Journal of Advanced Corporate Learning (iJAC), 2011)
With the facility to connect people and information around the world, the Internet is before now having a major impact on the traditional education. Currently, students can easily access the online course materials anytime anywhere. Internet also amplifies the complication of the course materials development. As the learning idea is taken by a student in the e-learning environment, traditional teacher determined learning model is no longer appropriate. As a result, student-centered course materials which are prepared based on individual studentâ??s learning expectation, styles, interests and individual academic background become critical. The quick growth of Internet technologies and web based environments, e-learning has become a major trend in the education area. Most of the e-learning contents are still developed in same traditional educational ways; Jordanian government Universities followed a different ways in implementing e-learning systems. The objective of this research is to understand the extent of E-learning implementation practices currently in use. To achieve this objective, a survey of E-learning implementation practice in Jordanian universities was conducted. A detailed description of the survey procedures is provided in this paper. The units of analysis for the survey were Jordanian government universities undertaking E-learning systems implementations. The target population included all Jordanian government universities which implement E-learning systems by second party as well as in-house e-learning system development. The results showed that there is a weakness in applying E-learning implementation practices in Jordanian government universities. The results of the study lead to important recommendations to improve E-learning implementation practice in Jordanian government universities in Jordan like that the development teams should be multidisciplinary and universities should pay attention to the quality management and standards. The results also compared to some case studies from European countries. The analysis also showed that there are significant differences in the levels of adoption of E-learning implementations practices between European universities and Jordanian government universities.